(untitled) (Medical Forum Monthly, 2020)
Objective: To compare the outcomes of mini plate versus K-wire fixation in patients undergoing surgical treatment for fractures shaft of metacarpal. Study Design: Randomized controlled trial study. Place and Duration of Study: This study was conducted at the Department of Orthopaedics, Nishtar Hospital Multan from January 2019 to June 2020. Materials and Methods: Forty patients of both genders presented with fractures shaft of metacarpal were enrolled. All the patients were divided equally in to two groups. Group I with 20 patients received mini plate internal fixation and group II with 20 patients received K-wire fixation. Functional outcomes were analyzed by DASH scoring system. Post-operative complications were examined. Results: In group I, 12 (60%) patients were male and 8 (40%) were females with mean age 32.22±8.96 years and in group II 13 (65%) were male and 7 (35%) were females with mean age 33.86±7.48 years. In group I, 13 (65%) patients had excellent, 4 (20%) had good, 2 (10%) had fair and 1 (5%) had poor functional outcomes, in group II 7 (35%) patients had excellent, 7 (35%) had good 4 (20%) had fair and 2 (10%) had poor functional outcomes as per DASH criteria. In group I, 2 (10%) patients and in group II 4 (20%) patients had developed postoperative complications. Conclusion: Internal fixation with miniplate for shaft of metacarpal fractures showed better functional outcomes with fewer rate of postoperative complications and earlier union as compared to K-wire internal fixation.